The economic impact of the African Refining Agency on Algeria: a forward-looking vision (مجلة إضافات إقتصادية, 2025)
This study aims to explore the economic impact of the African Rating Agency on African countries in general, and Algeria in particular. This study relies on a descriptive and analytical approach, examining the most important events and repercussions of the establishment of this agency. It then analyzes the current state of the Algerian economy and explores the agency's impact on the Algerian economy. The study concluded that this agency has become a necessity, not an option, and that it will have many positive effects on the Algerian economy, but all of this depends on the availability of the necessary capabilities and conditions for  this.Jel Classification Codes: G24, O55, H63